Application of the ideal profile method to identify an ideal sufu for nonregular consumers. (22nd March 2018) - Chen, Yan Ping; Chung, Hau Yin
Abstract: BACKGROUND: Sufu is a fermented soybean food with unique odor, flavor, and texture, which might not be appreciated by nonregular consumers. To identify the attributes that nonregular consumers appreciated, 12 commercial products bought from a Hong Kong market were tested by 113 consumers according to the ideal profile method (IPM), and rated on 22 attributes. RESULTS: Data provided from nonregular consumers were consistent at both panel and consumer levels. The predicted ideal profile received a higher hedonic score (7.0) than the tested products (6.0). Compared with commercial samples, the ideal sufu has low intensity in the attributes of fermented (aroma and flavor), moldy (aroma), and hard (texture), but high intensity in the soybean‐like (aroma and flavor) and sesame oil‐like (aroma and flavor) attributes. CONCLUSION: IPM could be used as an alternative approach to collect sensory profiles and preference data directly from consumers for product characterization. It could also be applied to identify the attributes that nonregular consumers appreciated. © 2018 Society of Chemical Industry